Pembentukan Pribadi Disiplin Dalam Implementasi Ekstrakurikuler Pramuka Di SDN 2 Tirem Grobogan - Kardi, Kardi, Prof.Dr,Sutama,M.Pd, Dr.Suyatmini,M.S.i (2016)
The purpose of this research is 1) To know the implantation personal discipline by habituation in the implementation of extracurricular Scout in SDN 2 Tirem, 2) To determine the implantation Personal discipline by example in the implementation of extracurricular scout in SDN 2 Tirem, 3) To know the constraints implantation personal discipline in pramuka extracurricular implementation at SDN 2 Tirem. This research is kualitatif.Teknik collection of data through observation, interviews and documentation. Data analysis technique performed with data collection, data reduction, data presentation, and conclusion. Test the validity of the data in this study using triangulation sources. The results of this study were 1) Activity scout in SDN 2 Tirem to plant the discipline of students with pembiasaaan with the activities of opening and closing ceremonies in every activity, Obeying the discipline in kegitatan extracurricular scout SDN 2 Tirem, existence of activities Regulation Line-lined (UN) , semaphore and morse 2) Supervising scout SDN 2 Tirem provide an example to the students in extracurricular activities with the scouts were present before the activity takes place, the school principal scout watching the course of extracurricular activities. The participation of parents is a role model for students by providing support to students in participating in scouting activities, parents as school partners. 3) inhibiting factors encountered in the planting of personal discipline in the implementation of extracurricular pamuka in SDN 2 Tirem terltak on technical factors where the extracurricular activities took place late in the evening that the majority of children used as a time for rest, school recite or play, when it entered the time of the rainy many students who do not follow the permission to scout extracurricular activities, funding factor. The impact of the barriers, implementation of extracurricular becomes the maximum, the material presented by the Trustees scout unevenly received by students that led to the planting of personal discipline in the implementation of extracurricular pamuka in SDN 2 Tirem not been in line with expectations. To overcome the existing problems in extracurricular activities scouts in SDN 2 Tirem, with the holding of the evaluation at the end of the scouts so much easier to know the problems-problems that exist so that the improvements and the planting of discipline of the scouts can be applied by students both within the school and residence